Performance Analysis of Three Phase Induction Motor based on ATV12HU15M2 Inverter for Control System Practicum Module - Chico Hermanu Brillianto Apribowo; Mohammad Hakim Adhiguna; Feri Adriyanto; Hari Maghfiroh (Journal of Electrical, Electronic, Information, and Communication Technology, 2020)
Understanding that electrical engineering graduates who have experience and are able to know the electric power system in the industry are the main thoughts of the writer to conduct research. Through the manufacture of a three-phase ac motor control practicum module, which is the type of motor most often used in industrial activities, is expected to provide more knowledge to prospective graduates of electrical engineering engineers. The author determines the two previous research categories chosen as references, namely the training of electric motor modules and the final project of electrical engineering students. In this study the ATV12HU15M2 inverter is used to control changing the frequency value as an input variable to determine its effect on output variables such as voltage, current, power, rpm, and THD. Equipped with SoMove software that is connected to the laptop to be able to change the value of input variables such as motor power, number of poles, and power factors to match the specifications of the electric motor used, the software can also monitor if an error occurs in the system. At the measurement stage, the measuring instrument used is a Power Analyzer to measure the input power of a single-phase system at the source grid PLN, the output power of a three-phase electric motor system, and experimental measurements of motors coupled with a dc generator. For the purposes of data processing, DataView software is used to display the measurement results into a laptop, the resulting display can be in the form of a waveform graph, a graph of THD occurrence, and power information for which the displayed data can be stored. The THD result most optimal at 50Hz frequency with THDv value 18.69% and THDi value 9.04%.